Sports career analysis of Olympic champions in Greco-Roman wrestling. - Latyshev, M.; Tropin, Y. (Edinoborstvo, 2020)
Purpose: to analyze the appearances of the champions of the Olympic Games in Greco-Roman wrestling. Material and methods. Our study used the following methods: analysis of scientific and methodological information and Internet sources; generalization of best practices;analysis of official competition protocols; methods of mathematical statistics; analysis, synthesis and modeling of individual aspects of the competitive activity of wrestlers. The sports careers of all the winners of the six Olympic Games in Greco-Roman wrestling from 1996 to 2016 were studied. A total of 45 sports biographies were analyzed, they include the performances of wrestlers in official international competitions. The initial performance data was taken from the official site of the international wrestling federation United World Wrestling (unitedworldwrestling.org). Results: It was established that the improvement of the sportsmanship of Olympic wrestlers should be based on strict individualization of the training process, taking into account the requirements of competitive activity. The analysis of sports biographies of elite wrestlers of the Greco-Roman style was carried out, on the basis of which the data on the indicators of champions at the Olympic Games 1996, 2000, 2004, 2008, 2012, 2016 in retrospect were obtained, they are necessary to justify the plans of sports activities of wrestlers for the future. It was determined that the age of the beginning of a sports career is decreasing: from 19,1 years (1996 Olympic Games) to 17,3 years (2016 Olympic Games). The same trend is observed with the average age of retirement - decreased from 33,2 years (1996 Olympic Games) to 30,8 years (2008 Olympic Games). It was revealed that in order to predict sports performance and the formation of a sports career, the period of adult struggle before winning the Olympic Games is most important. Conclusions. Àn analysis of the performances of the champions of the Olympic Games in Greco-Roman wrestling showed that the number of official competitions of the international level in which athletes took part in each Olympic cycle increases from 28,1 competitions (1996 Olympic Games) to 41,2 competitions (Olympic Games 2016). Most athletes (84,2 %) win only once at the Olympic Games and participate once or twice (97,4 %), so it is extremely important to approach the Olympic Games in the best fit.